Cartoon-based message strategies on vaccination in Romania and engagement behavior. A multimodal approach. - Camelia Cmeciu (Romanian Journal of Communications and Public Relations)
This study investigates the influence of Romanian cartoons related to COVID-19 vaccination on online engagement. Humor has been employed by (inter)national authorities in order to simplify complex issues and to encourage positive attitudes and behaviors toward certain health issues. Focusing our analysis on the cartoons employed by two Romanian authorities (CNCAV and European Commission’s Representation in Romania), the aims of this study are threefold: to determine how Health Belief Model constructs and humor types influenced the online users’ online engagement behavior towards the cartoons on vaccination in Romania; to identify how multimodal modes were employed in the cartoons on COVID-19 vaccination; to determine how knowledge resources help in the interpretation of humor in the overperforming multimodal cartoons. The findings showed that commenting was significantly triggered by cartoons embedding more cues to action than self-efficacy. Perceived barriers generated significantly more laughter than perceived benefits, more sad reactions and less angry reactions than cues to action. Despite the high frequency of irony and pun as humor types, aggressive humor (sarcasm or satire) triggered more Romanian users to interact with cartoons as a creative message strategy and the humorous representations of the anti-vaxxers and the undecided on both Facebook accounts scored higher in terms of engagement metrics.